A Study of School Principals' Practices to Ensure Teacher Accountability for Curriculum Implementation in Ethiopian Primary Schools - Urga, Feyera Beyessa; Kenea, Ambissa (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2023)
This study investigates the curriculum implementation practices of principals in public elementary schools in East Wollega Zone, Ethiopia. Using an exploratory case study approach and a multiple case study research design, data were collected through semi-structured interviews and document review, and analyzed using thematic analysis. The results of the study confirm that principals prioritize holding teachers accountable for tasks other than curriculum implementation in the classroom. They pay insufficient attention to curriculum implementation while effectively managing subordinate accountability. The research reveals that stringent actions, such as removal from promotion and salary cuts, are imposed when teachers' performance in subordinate tasks declines. When teachers are present at schools, their shortcomings in implementing the curriculum are usually addressed by moving them to lower grades instead of imposing harsh punishments. In contrast, sanctions such as fines equivalent to three months' salary, demotion, and dismissal are reserved exclusively for violations of the teachers' code of ethics, not for performance issues in the classroom. Based on the findings, the study suggests that the government create a fresh educational accountability policy. This policy should motivate school principals to emphasize and strengthen accountability for executing the curriculum successfully.